(untitled) (Cadernos de Sociomuseologia, 2019)
This thesis has as its starting point the analysis of the situation we are currently facing a considerable part of the museums in Guantanamo , the easternmost of the Cuban provinces , marked by the absence to date of a strategy organically structured to guide in a manner consistent interaction of the institutions of the Provincial Museum System Guantanamo with their social environments to help strengthen in some cases and redirect others, the social dimension of the dynamics operating Guantanamo museums. On the budgets of the sociomuseologia, has proposed a strategy to ensure that the SPMG achieve greater insertion the development of the communities where they are located so that adequately meet the social responsibility that are called these institutions with their respective social contexts. Keywords: Museum, Museology (Sociomuseología), Provincial Museum System Guantanamo, Community and Strategy.